1996
DOI: 10.1037/0021-9010.81.5.512
|View full text |Cite
|
Sign up to set email alerts
|

Task frequency rating accuracy: The effect of task engagement and experience.

Abstract: In this study, researchers examined the effect of task engagement and experience on frequency rating accuracy with an objective measure of task frequency. By contrasting findings from the memory literature on frequency estimation with current task analysis practices, these investigators proposed that task performers and respondents with low levels of experience would generate more accurate frequency estimates compared with task observers and respondents with high levels of experience. Participants were randoml… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 60 publications
0
16
0
Order By: Relevance
“…The research on SME job tenure has yielded mixed results, with some finding important differences as a function of tenure (Borman et al, 1992;Goldstein, Noonan, & Schneider, 1992;Landy & Vasey, 1991;Richman & Quinones, 1996;Tross & Maurer, 2000), while others finding no difference (Cornelius & Lyness, 1980;Green & Stutzman, 1986;Mullins & Kimbrough, 1988;Schmitt & Cohen, 1989). Most of this research focused on task ratings though, with only two studies comparing KSAO ratings (Goldstein et al, 1992;Tross & Maurer, 2000).…”
Section: Sme Job Tenure and Accuracymentioning
confidence: 99%
See 1 more Smart Citation
“…The research on SME job tenure has yielded mixed results, with some finding important differences as a function of tenure (Borman et al, 1992;Goldstein, Noonan, & Schneider, 1992;Landy & Vasey, 1991;Richman & Quinones, 1996;Tross & Maurer, 2000), while others finding no difference (Cornelius & Lyness, 1980;Green & Stutzman, 1986;Mullins & Kimbrough, 1988;Schmitt & Cohen, 1989). Most of this research focused on task ratings though, with only two studies comparing KSAO ratings (Goldstein et al, 1992;Tross & Maurer, 2000).…”
Section: Sme Job Tenure and Accuracymentioning
confidence: 99%
“…Incumbents also demonstrated the lowest intra‐rater reliability. On the other hand, Richman and Quinones () found that incumbents were more accurate than observers (pseudo supervisors) when rating task frequency. Others (Manson, Levine, & Brannick, ; Sanchez, ) have found there to be little difference between incumbents and supervisors across task inventory ratings, leading them to conclude that the choice of respondent will have little impact on results.…”
Section: Introductionmentioning
confidence: 99%
“…A wide range of variables has been examined for their potential relationships to requirement ratings within work analysis research. For example, research has investigated variables such as demographics and work experience (e.g., Landy & Vasey, 1991; Tross & Maurer, 2000), job satisfaction and involvement (e.g., Conte, Dean, Ringenbach, Moran, & Landy, 2005), job performance (e.g., Conley & Sackett, 1987; Sanchez, Prager, Wilson, & Viswesvaran, 1998), and task engagement or liking (e.g., Love, Bishop, & Scionti, 1991; Richman & Quinones, 1996). Unfortunately, the general consensus regarding the findings of this extensive empirical exploration is that the collective results have been rather equivocal (Dierdorff & Wilson, 2003).…”
mentioning
confidence: 99%
“…The specificity of work experience can be captured at the task, job, and organization levels using operationalizations of amount (e.g., number of times a task was performed), time (e.g., job tenure), and type or quality of experience (Quiñones, Ford, & Teachout, 1995). Richman and Quiñones (1996) further emphasized the importance of how work experience is assessed and noted that simple measures of job tenure, although prevalently used, provide only a narrow definition of work experience. In our study, work experience was assessed using two modes of measurement at the job level of specificity: amount of actual work role experience and the length of time spent in the work role.…”
Section: Work Experiencementioning
confidence: 99%